2004
DOI: 10.1074/jbc.m309978200
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei Plasma Membrane-Type Ca2+-ATPase 1 (TbPMC1) and 2 (TbPMC2) Genes Encode Functional Ca2+-ATPases Localized to the Acidocalcisomes and Plasma Membrane, and Essential for Ca2+ Homeostasis and Growth

Abstract: Trypanosoma brucei adaptation and survival in its host involve integrated regulation of Ca 2؉ pumps (Ca 2؉ -ATPases), which are essential in calcium ion homeostasis. Here we report the cloning and sequencing of two genes (TbPMC1 and TbPMC2) encoding plasma membrane-type Ca 2؉ -ATPases (PMCAs) of T. brucei, an agent of African trypanosomiasis. Indirect immunofluorescence analysis using antibodies against the proteins and against epitope tags introduced into each protein showed that TbPMC1 co-localized with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 45 publications
(62 reference statements)
1
57
0
Order By: Relevance
“…However this organelle accumulates also Ca and other divalent cations such as Zn and Fe which co-precipitates with large amounts of polyphosphates. For this reason, they have been suggested to participate in several cellular processes such as osmoregulation [37], storage of high-energy polyphosphate for mobilization in case of stress or great energy demands [47,48], in pHstasis [23] and the Ca 2+ homeostasis [25,49]. We have previously shown that the endoplasmic reticulum of Herpetomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…However this organelle accumulates also Ca and other divalent cations such as Zn and Fe which co-precipitates with large amounts of polyphosphates. For this reason, they have been suggested to participate in several cellular processes such as osmoregulation [37], storage of high-energy polyphosphate for mobilization in case of stress or great energy demands [47,48], in pHstasis [23] and the Ca 2+ homeostasis [25,49]. We have previously shown that the endoplasmic reticulum of Herpetomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, most cells had reduced motility, and formation of cell debris was observed, mostly at days 6-8, suggesting cell death (data not shown). Growth resumed after z9 d and was accompanied by the reappearance of KREPA6 protein based on Western analysis (data not shown), suggesting loss of KREPA6 repression as sometimes observed (for example, see O'Hearn et al 2003;Luo et al 2004). Quantitative real-time RT-PCR (qPCR) analysis indicated that the level of KREPA6 mRNA was reduced substantially (Fig.…”
Section: Krepa6 Is Important For Growth and In Vivo Rna Editingmentioning
confidence: 99%
“…Acidic stores include lysosomes (Lloyd-Evans et al, 2008;Churchill et al, 2002), secretory lysosomes (Holmsen and Weiss, 1979), acidocalcisomes (Luo et al, 2004) and vacuoles (Patel and Docampo, 2010). Moreover, recent studies have demonstrated that such pools are also mobilisable (Churchill et al, 2002;Lange et al, 2009).…”
Section: Introductionmentioning
confidence: 99%